Pengaruh Gaya Komunikasi Kepemimpinan Transformasional terhadap Kinerja Karyawan di Lingkup Perkantoran Modern - Praminiarti, Irma Dwi; Satya, Muhammad Dani; Ramadhan, Dani (Komunika : Jurnal Ilmiah Komunikasi, 2024)
The modern office environment requires innovative leadership approaches to improve employee productivity and performance. This research aims to see how transformational leadership style affects employee performance. The study will focus on four main dimensions: idealised influence, inspirational motivation, intellectual stimulation and individualised attention. Furthermore, this study also investigates the function of work motivation as a supporting component in enhancing the relationship between performance and leadership. The research method used a quantitative approach with a survey involving 103 respondents from companies in Surabaya. Data were collected through a 5-point Likert scale-based questionnaire and analyzed using simple linear regression test. The results showed that transformational leadership style has a positive and significant impact on employee performance with a regression coefficient of 0.325 and a significance level of 0.000 (<0.05). As much as 15.5% of employee performance variability is explained by transformational leadership style, while the rest is influenced by other factors. Leaders who provide motivation, appreciation, and inspiration are proven to increase productivity, job satisfaction, and collaboration in the workplace. Implementation of an ideal transformational leadership style requires ongoing leadership training and an inclusive work culture. This research recommends the development of studies that examine the influence of local culture and other sectors to expand the generalizability of the findings.